Analysis of Otorhinolaryngological Manifestations in Patients Diagnosed with Traumatic Brain Injury - Khalid Mahmood Khan, Zahid Khan, Sohail Ahmad, Sajid Khan, Abdul Hafeez Baloch, Sabika Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Even though otorhinolaryngological injuries are relatively common, they are occasionally neglected, missed, and overlooked. Objective: The study aimed to analyze the Otorhinolaryngological manifestations in patients suffering from brain injury admitted in tertiary care unit. Study design: This analytical study was conducted at the Neurosurgery Department of Lady Reading Hospital Peshawar and Neurosurgery Department of Prime Teaching Hospital Peshawar for the duration of the six months from August 2021 to January 2022. Material and Methods: There were 448 patients that were admitted in the tertiary care unit with complaint of head injury. Only 365 patients fulfilled the inclusion criteria. The ethical and review board committee of our hospital approved the study. The written consent was taken from the patients. Results: There were 75 (25%) patients who were linked with ENT manifestation. The patients having ENT manifestations included more male than female. The average age of the patients was 37.3 ± 15.3 years. The 52% came with minor injury in the head. It was seen that recovery rate was quite good in case of patients having ENT manifestations. Conclusion: In case of head injuries ENT injuries are seen commonly. Injuries in the soft tissues of nose, ear and face are some of the commonly observed findings some other findings like CSF rhinorrheas was also observed. There was no prominent link of ENT injury with the overall impact of hospital stay of the patients and the head injury. Keywords: CSF rhinorrheas and Otorhinolaryngological manifestations.